Spatial Variable in the Contemporary Digital Theater Show "Cirque du Soleil" as a Model (Al-Academy, 2025)
The spatial variable constitutes the spirit of the show for the director in order to activate the element of suspense for the recipient through its aesthetic features that call for multiplicity and diversity in order to create a new composition for the show. Therefore, the researcher studied this spatial variable and divided it into four chapters. In the first chapter, the researcher defined the problem of his research in the following question (What is the spatial variable in the contemporary digital theatrical show "Cirque du Soleil" as a model?) and the importance of the research as it is an important study for specialists in the theatrical arts at the level of directing, in addition to the goal of the research (revealing the spatial variable of the contemporary digital theatrical show "Cirque du Soleil" as a model) and the limits of the research and defining the terms included in the research topic. In the second chapter, the theoretical framework was divided by the researcher into two sections. The first section dealt with (the philosophy of place), in which the researcher reviewed the most important philosophies that dealt with place materially and ideally. The second section (digital technology and theatrical coupling), in which the researcher reviewed the starting points of digital technology in the theater and how it achieved the integrated reality in the theatrical performance. Then the chapter concluded with the most prominent indicators that resulted from the theoretical framework. In the third chapter, the research procedures that included the intentional research sample (Worlds Away Cirque du Soleil) and the reasons for choosing it, in addition to the descriptive analytical research methodology. The chapter concluded with an analysis of the sample. In the fourth chapter, the research results. After analyzing the sample, the researcher reached the results and conclusions, in addition to the recommendations and suggestions, a list of sources and references, and a summary of the research in both Arabic and English